Busy woman's checklists - Tatsui-D'Arcy, Susan (Prentice Hall, 1998)
Busy women can pack this small book into a briefcase, diaper bag, purse, or desk. Pared down to the essentials, it provides all the checklists, calendars, and worksheets needed to organize all those important events in a hectic life.